2018
DOI: 10.5897/jssem2018.0691
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of soils under major land uses in Chencha District, South Ethiopia

Abstract: Assessing land use induced changes in soil properties is essential for addressing the issues of land use planning and sustainable land productivity in highlands of Ethiopia. The surface and profile soil samples were collected from forest (FL) cultivated (CL) and grass/pasture lands (GL) in Doko Yoyira (DY), Aiezo Tula (AT) and Gendona Gembela (GG) in Chencha district, Gamo-Gofa zone in May 2014, which aims to assess different soil physicochemical properties. At surface layer of 0-20 cm, the results did not sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The study area is found in Ethiopia's main rift valley, which features a gently undulating plain surrounded by mountains and ridges and Lake Chamo. Its landscape is characterized by dissected slopes, tectonic processes, and external erosion [ 15 ]. The minimum monthly temperature is 14.5 °C, while the maximum monthly temperature is 33.3 °C in the catchment area.…”
Section: Methodsmentioning
confidence: 99%
“…The study area is found in Ethiopia's main rift valley, which features a gently undulating plain surrounded by mountains and ridges and Lake Chamo. Its landscape is characterized by dissected slopes, tectonic processes, and external erosion [ 15 ]. The minimum monthly temperature is 14.5 °C, while the maximum monthly temperature is 33.3 °C in the catchment area.…”
Section: Methodsmentioning
confidence: 99%